PERSEPSI GENERASI Z KOTA SURABAYA MENGENAI REWARD PADA APLIKASI SNACKVIDEO: PERSEPSI GENERASI Z KOTA SURABAYA MENGENAI REWARD PADA APLIKASI SNACKVIDEO - Ramadani, Alfina; Sukardani, Puspita Sari (The Commercium, 2023)
This study aims to find out how the perception of Generation Z Surabaya City about the reward on SnackVideo application. This study is a qualitative descriptive research with phenomenology approach. The paradigm used in this study is constructivism, where everyone can interpret things differently from others, based on their environment, views and experiences. Data collection in this study was conducted through in-depth interviews. The results of this study showed that the entire generation Z of Surabaya city as SnackVideo users have a positive perception of the reward. Generation Z has a view that rewards on the SnackVideo app are attractive and profitable. The whole generation Z also considers that the reward is instant, by playing social media they get a profitable reward. Keywords: Generation Z, Reward, SnackVideo, Instant Stuff